Democratic Attitudes of Prospective Teachers - Gömleksiz, Mehmet Nuri; Çetintaş, Sare (Dicle Üniversitesi, 2011)
One of the most important functions of any educational system is to bring up democratic individuals. Democracy survives and develops only in the societies formed of people who have grasped it as behaviour and who can apply its principles their lives. Maintaining democracy will be possible by bringing up individuals who accept democratic values. The purpose of this research is to assess the democratic attitudes of prospective teachers enrolled in Education Faculties. "Democratic Attitude Scale" adapted into Turkish by Gözütok (1995) was used in the study. Democratic attitudes of prospective teachers differed significantly in terms of gender, university, department, education level of their mothers, economic status of their parents and number of sibling but did not differ in terms of education level of thei father

Eğitim sistemlerinin en önemli işlevlerinden birisi demokratik bireyler yetiştirmektir. Demokrasi ancak demokrasiyi davranış biçimi olarak özümsemiş ve demokrasi ilkelerini yaşama uygulayabilmiş insanlardan oluşan toplumlarda yaşamakta ve gelişmektedir. Demokrasiyi yaşatma, demokratik değerleri benimsemiş bireyleri yetiştirmekle mümkündür. Bu araştırmanın amacı Eğitim Fakültelerinde öğrenim gören öğretmen adaylarının demokratik tutumlarını belirlemektir. Araştırmada Gözütok (1995) tarafından Türkçeye uyarlanan ”Demokratik Tutum Ölçeği” kullanılmıştır. Öğretmen adaylarının demokratik tutumları cinsiyet, üniversite, bölüm, anne eğitim düzeyi, gelir düzeyi, kardeş sayısı değişkenleri açısından farklılaşırken, baba eğitim düzeyine göre farklılaşmanın olmadığı tespit edilmiştir.
ÖĞRETMEN ADAYLARININ DEMOKRATİK TUTUMLARI
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar